Factors Associated With Emergency Services Use by Patients With Recurrent Myocardial Infarction: From the Monitoring Trends and Determinants in Cardiovascular Disease/Cooperative Health Research in the Region of Augsburg Myocardial Infarction Registry. Issue 4 (July 2017) - Kirchberger, Inge; Amann, Ute; Heier, Margit; Thilo, Christian; Peters, Annette; Meisinger, Christa
Abstract : Background: Although emergency medical services (EMS) use is the recommended mode of transport in case of acute coronary symptoms, many people fail to use this service. Objective: The objective of this study was to determine factors associated with EMS use in a population-based sample of German patients with recurrent acute myocardial infarction (AMI). Methods: The sample consisted of 998 persons with a first and recurrent AMI, recruited from 1985 to 2011. Logistic regression modeling adjusted for sociodemographic, situational, and clinical variables, previous diseases, and presenting AMI symptoms was applied. Results: Emergency medical services was used by 48.8% of the patients at first, and 62.6% at recurrent AMI. In first AMI, higher age, history of hyperlipidemia, ST-segment elevation AMI, more than 4 presenting symptoms, symptom onset in daytime, and later year of AMI were significantly related with EMS use. Pain in the upper abdomen and pain between the shoulder blades were significantly less common in EMS users. In recurrent AMI, EMS use at first AMI, presence of any other symptom except chest pain, ST-segment elevation myocardial infarction, and later year of AMI were significantly related with EMS use. Significant predictors of EMS use in recurrent AMI in patients who failed to use EMS at first AMI were unmarried, experience of any symptom except chest symptoms at reinfarction, bundle branch block (first AMI), any in-hospital complication (first AMI), longer duration between first and recurrent AMI, and later year of reinfarction. Conclusions: Patients with AMI and their significant others may profit by education about the benefits of EMS use.